PORTADA, EDITORIAL SISANH 2021 - Pucuna, Saul Yasaca (La Ciencia al Servicio de la Salud y la Nutrición; Vol. 12 Núm. SISANH (2021): Edición Especial SISANHDO - 10.47244/cssn.Vol12.IssSISANH.660, 2022)
Portada